Study on the solar energy absorption of hybrid solar cells with trapezoid-pyramidal structure based PEDOT:PSS/c-Ge. (1st July 2020) - Zhao, Fei; Chen, Xifang; Yi, Zao; Qin, Feng; Tang, Yongjian; Yao, Weitang; Zhou, Zigang; Yi, Yougen
Graphical abstract: We report a numerical study of an ideal PEDOT:PSS/c-Ge Hybrid Solar Cells with trapezoidal pyramids structure (As shown in Fig. (a)). By optimizing the design, the average absorption efficiency in the AM 1.5 spectrum within the wavelength ranged from 300 nm to 1500 nm has reached 93.8% (As shown in Fig. (b)). When the ratio of top to bottom of the trapezoidal pyramids is 1/16 (T/B = 1/4, h = 300 nm), the Jsc is up to 43.47 mA/cm 2 (As shown in Fig. (c)) and the maximum power is 7.9 mW/cm 2 (As shown in Fig. (d)). Highlights: The optical absorption of trapezoid-pyramidal HSCs is above 90% in the range of sunlight. The average absorption of trapezoid-pyramidal HSCs is 93.8% under AM 1.5 solar spectrum. The short circuit density of trapezoid-pyramidal HSCs has reached to 43.47 mA/cm 2 . The trapezoid pyramid has a good light capture effect. Abstract: In this paper, we have utilized finite difference time domain (FDTD) method to investigate the solar energy absorption of hybrid solar cells (HSCs) with trapezoid-pyramidal structure (TPs) based PEDOT:PSS/c-Ge. We have changed some parameters of TPs (different heights and different ratios of top to bottom) to study its effects on the solar energy absorption for HSCs. The optimization of geometric parameters is based on the maximum solar energy absorption efficiency. The optical absorption of the HSCs with TPs is basically above 90% from 300 nm to 1300 nm and the average solar energy absorption is 93.8% under AM 1.5 solar spectrum (from 300 nm to 1500 nm). Simultaneously, we have calculated the short-circuit current density (Jsc ), open-circuit voltage (Voc ), fill factor (FF), maximum power (Pmax ) and photoelectric conversion efficiency (PCE) respectively through DEVICE software. The results of electrical simulation reveal that the maximum Jsc is 43.47 mA/cm 2, it is 45.73% higher than planar PEDOT:PSS/c-Ge HSCs. Moreover, to further explain the mechanism of solar energy absorption of HSCs with TPs, the logarithmic figures of electric field intensity for trapezoid-pyramidal PEDOT:PSS/c-Ge HSCs and planar PEDOT:PSS/c-Ge HSCs at different wavelengths are analyzed. The result shows that TPs array has shown excellent light-trapping effect. This work reveals the huge potential of c-Ge HSCs in solar absorption, and at the same time has certain guiding significance for the structural design of Ge SCs. It is believed that through further exploration, the conversion efficiency of c-Ge HSCs will be further improved.